2010
DOI: 10.1002/ajmg.b.31090
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of the heterogeneity in association of DRD4 7‐repeat allele and AD/HD: Stronger association with AD/HD combined type

Abstract: The purpose of this meta-analysis was to examine whether association studies between attention deficit/hyperactivity disorder (AD/HD) and the dopamine receptor 4 gene 7-repeat (DRD4 7R) allele vary systematically based on study characteristics. A total of 27 empirical studies with 28 distinct samples using either case-control or family-based association analyses were included. Consistent with previous meta-analytic work [Gizer et al. (2009), Hum Genet 126:51-90], the DRD4 7R allele was associated with AD/HD ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 85 publications
2
25
0
3
Order By: Relevance
“…Our results are in agreement with previous studies supporting the validity of the different DSM-IV subtypes, mainly the combined subtype, and suggesting the participation of differential genetic factors in distinct ADHD clinical groups [Rasmussen et al, 2004;Larsson et al, 2006;Sobanski et al, 2008;Ribases et al, 2009]. Interestingly, Smith [2010] performed a meta-analysis of 28 association studies between ADHD and the 48bpVNTR in DRD4 and observed that increases in the proportion of combined ADHD patients within an ADHD sample were associated with an increase in the magnitude of the effect. These results are consistent with the hypothesis that DRD4 is more strongly associated with combined ADHD than with inattentive ADHD and are in line with the hypothesis that hypofunctioning in mesocortical and mesolimbic dopaminergic pathways better characterize the etiology of combined ADHD than inattentive ADHD [Sagvolden et al, 2005;Smith, 2010].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are in agreement with previous studies supporting the validity of the different DSM-IV subtypes, mainly the combined subtype, and suggesting the participation of differential genetic factors in distinct ADHD clinical groups [Rasmussen et al, 2004;Larsson et al, 2006;Sobanski et al, 2008;Ribases et al, 2009]. Interestingly, Smith [2010] performed a meta-analysis of 28 association studies between ADHD and the 48bpVNTR in DRD4 and observed that increases in the proportion of combined ADHD patients within an ADHD sample were associated with an increase in the magnitude of the effect. These results are consistent with the hypothesis that DRD4 is more strongly associated with combined ADHD than with inattentive ADHD and are in line with the hypothesis that hypofunctioning in mesocortical and mesolimbic dopaminergic pathways better characterize the etiology of combined ADHD than inattentive ADHD [Sagvolden et al, 2005;Smith, 2010].…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, Smith [2010] performed a meta-analysis of 28 association studies between ADHD and the 48bpVNTR in DRD4 and observed that increases in the proportion of combined ADHD patients within an ADHD sample were associated with an increase in the magnitude of the effect. These results are consistent with the hypothesis that DRD4 is more strongly associated with combined ADHD than with inattentive ADHD and are in line with the hypothesis that hypofunctioning in mesocortical and mesolimbic dopaminergic pathways better characterize the etiology of combined ADHD than inattentive ADHD [Sagvolden et al, 2005;Smith, 2010]. This view is supported by the fact that variation in DAT1, another dopaminergic gene, is also more strongly associated with combined ADHD than with inattentive ADHD (e.g., Waldman et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, genes associated with monoamine neurotransmission have been implicated in its pathogenesis. Although significant research has focused on associations between inattention and hyperactivity symptom phenotypes and polymorphisms in genes such as dopamine receptors [15] or dopamine transporter [16], recent interest has been directed at the potential role of the serotonin transporter length polymorphism present in the promoter region of the gene that codes for the serotonin transporter (5-HTTLPR), at least in the case of home-reared children. This is one of two reasons why we focus on this polymorphism in the current inquiry.…”
Section: Genetics and Adhdmentioning
confidence: 99%
“…Clearly, there is considerable ambiguity with regard to the role of DRD4 VNTR in nicotine dependence, and there is a need for larger, more systematic studies to clarify this relationship. Notably, a further complication is that the DRD4 7-repeat allele has most robustly been associated with attention deficit/hyperactivity disorder (ADHD) (Faraone, Doyle, Mick, & Biederman, 2001;Smith, 2010), which itself is linked to smoking (McClernon & Kollins, 2008), but most studies on the link between DRD4 VNTR and smoking do not integrate ADHD status or symptoms. In this study, individuals with a current ADHD diagnosis were excluded, but subclinical or undiagnosed individuals may have enrolled, a limitation that applies to virtually all studies in this area.…”
Section: Discussionmentioning
confidence: 99%